Artificial Intelligence Governance Strategy in the Indonesian Regulation System, Offensive or Defensive? - Maria, Indri; Riswadi, Riswadi (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The Indonesian government unveiled its National Strategy on Artificial Intelligence (AI) in 2020, known as “Strategi Nasional Kecerdasan Artifisial”. This comprehensive plan addresses various aspects of AI, including ethical considerations, policy frameworks, workforce development, data ecosystems, and infrastructure for AI advancement. It’s important to note, however, that National Strategy serves as a guiding policy document rather than a legally enforceable set of regulations. However, this does not mean that the Indonesian government is absent from regulating AI technology. In Indonesia, there are currently applicable regulations relating to the use of AI, although not directly confronting AI Technology. This qualitative journal aimed to analyze comparative strategies for drafting government regulations in the era of Artificial Intelligence. This journal was prepared using a normative approach, with laws and other valid legal bases as sources. The data for writing this article were obtained from a document or library study by studying and analyzing library materials and related regulations related to research problems. In conclusion, we will compare offensive strategies that focus on driving positive outcomes, such as increased opportunity and profitability, and defensive strategies that aim to prevent negative outcomes and reduce risks. The government can develop a comprehensive strategy that enables both offensive and defensive objectives or choose between offensive and defensive strategies.